Investigating the impact of exercise type combined with caloric restriction on quality of life–The PRONAF study - Ramos-Campo, Domingo Jesús; Rojo-Tirado, Miguel Ángel; Benito-Peinado, Pedro J. (Physiology & behavior, 2024)
•Any physical exercise intervention combined with caloric restriction, physical activity recommendations, and nutritional habits resulted in an enhancement of quality of life.•Only strength or strength in combination endurance training programs produced an improvement in emotional role.•No association between type of exercise, sex or age and dropping out or not was found. The aim of this study was to analyze the impact of endurance training (E), strength training (S), or combined training (SE), along with caloric restriction diet, compared to only diet and physical activity recommendations (C, control), on the quality of life in individuals with obesity. One hundred and twenty obese participants (61 males), aged 18–50 years, were randomly assigned to the different experimental groups, with ninety-six completing the study. The intervention period spanned 22 weeks (3 times per week). All subjects followed a hypocaloric diet, and quality of life was assessed using the SF36 questionnaire before and after the training program. A significant improvement was observed in emotional role following the S (Baseline: 85.06 ± 30.32; Post: 96.00 ± 11.06; p = 0.030) and SE (Baseline: 76.67 ± 35.18; Post: 91.30 ± 22.96; p = 0.010) programs, but not after E (Baseline: 83.33 ± 29.40; Post: 78.26 ± 35.69; p = 0.318) and C (Baseline: 77.01 ± 34.62; Post: 79.37 ± 37.23; p = 0.516). No significant main effect was observed in any other outcome measured. Overall, all groups demonstrated improvements in quality-of-life outcomes. In conclusion, any physical exercise intervention combined with caloric restriction, physical activity recommendations, and nutritional habits resulted in an enhancement of quality of life.